2011
DOI: 10.1590/s0103-50532011000100018
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-performance liquid chromatographic method for simultaneous quantification of HIV non-nucleoside reverse transcriptase inhibitors and protease inhibitors in human plasma

Abstract: Um método rápido para a determinação de seis inibidores de protease (indinavir, amprenavir, saquinavir, atazanavir, lopinavir e ritonavir) e de dois inibidores não-nucleosídicos da transcriptase reversa (efavirenz e nevirapine), empregando cromatografia líquida de ultra-eficiência com detector de arranjo de diodos foi desenvolvido e validado. Após extração liquido-líquido de 0,5 mL de plasma com metil-tert-butil éter, os analitos foram separados em uma coluna ACQUITY UPLC BEH ® C18 (2,1 × 150 mm, d.p. 1,7 µm),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Ultra performance liquid chromatography (UPLC) with diode array detection was the method used to determine ATV plasma concentrations. 11 After the liquid–liquid extraction of 0.5 mL of plasma with methyl- tert -butyl ether, the analytes were separated on a ACQUITY UPLC BEH ® C18 column (2.1 mm × 150 mm, p.d. 1.7 μm) eluted with a gradient of triethylammonium phosphate buffer pH 3.0 and acetonitrile.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultra performance liquid chromatography (UPLC) with diode array detection was the method used to determine ATV plasma concentrations. 11 After the liquid–liquid extraction of 0.5 mL of plasma with methyl- tert -butyl ether, the analytes were separated on a ACQUITY UPLC BEH ® C18 column (2.1 mm × 150 mm, p.d. 1.7 μm) eluted with a gradient of triethylammonium phosphate buffer pH 3.0 and acetonitrile.…”
Section: Methodsmentioning
confidence: 99%
“…In that context, higher plasma levels of the drug is one of the key factor that might contribute to the development of toxicity. 10 , 11 Therapeutic drug monitoring can be a useful weapon for dose adjustment in order to avoid concentrations that are out of the therapeutic range, thus preventing toxicity. 5 , 12 , 13 The purpose of this study was to assess the factors associated with plasma concentrations of ATV in HIV infected individuals with undetectable viral load in order to try to prevent toxicities attributed to this drug.…”
Section: Introductionmentioning
confidence: 99%
“…18 However, the coupling of UPLC to PDA detection allows fast analysis while keeping the advantages and robustness of UV detection modes, at a moderate cost. 19 In the present work, we validated a novel and fast UPLC-PDA assay for TDM of VRC in human plasma and oral fluid samples, after a simple liquid-liquid extraction.…”
Section: Introductionmentioning
confidence: 93%
“…Ritonavir (RTV), 2, 4, 7, 12-Tetraazatridecan-13oic acid, 10-hydroxy-2-methyl-5-(1-methylethyl)-1-[2-(1methylethyl)-4-thiazolyl]-3,6-dioxo-8,11-bis(phenylmethyl)-5-thiazolylmethyl ester [5S-(5R*,8R*,10R*,11R*)] is a potent cytochrcome P -450 (CYP)3A inhibitor and usually used as pharmacokinetic booster for other protease inhibitor including Atazanavir, thereby providing increased plasma level of Atazanavir 2 . Literature survey reveals High Performance Liquid Chromatographic (HPLC) [3][4][5][6][7][8][9] , LC-MS 10 and Ultra Performance Liquid Chromatography (UPLC) 11 methods for determination of ATV as single and in combination with other drugs in human plasma. Also Spectrophotometric method for degradation studies of ATV in dosage form has been also reported 12 .…”
Section: Introductionmentioning
confidence: 99%